The Effect Of Self-Efficacy, Personality And Social Media Use On Entrepreneurial Interests In Harapan University Students Medan - Sindy Nabila, Avicenna; Nahrisah, Ezzah; Pitono (Cattleya Darmaya Fortuna, 2025)
This study aims to analyze the influence of self-efficacy, personality and use of social media on entrepreneurial interest. The approach used in this study is a quantitative approach. The population in this study was 1896 students of Universitas Harapan Medan and the sample in this study used the 10% slovin technique so that a sample of 190 respondents was obtained. The sampling technique used stratified random sampling. In implementing this method, researchers used a questionnaire to obtain the necessary data because this method requires contact between researchers and respondents. The analysis technique used was multiple linear regression. The results showed that self-efficacy had a positive and significant effect on entrepreneurial interest. personality had a positive and significant effect on entrepreneurial interest. The use of social media had a positive and significant effect on entrepreneurial interest. Simultaneously, it shows that self-efficacy, personality and use of social media have a significant effect on entrepreneurial interest in Universitas Harapan Medan students. Suggestions for students to improve their ability in entrepreneurship, one way is to attend various seminars and training in order to develop self-quality in entrepreneurship